The Idea and Path of Cultivating Compound Business English Talents Under the Guidance of New Liberal Arts - Huang, Xian (Journal of Theory and Practice of Contemporary Education, 2024)
Guided by the primary task of new liberal arts building, this paper describes the core concepts of the positioning and talent training of interdisciplinary Business English program in the Teaching Guide for University Undergraduate Business English Program (hereinafter referred to as the Teaching Guide for Business English) from the aspects of the definition, educational objectives and training ways of interdisciplinary Business English talents, and proposes five composite training ways. It contributes to a better understanding and implementation of the Teaching Guide for Business English, and has important implications for the connotative, unique and innovative development of Business English program.